Bioactive and trackable MXene quantum dots for subcellular nanomedicine applications - Alireza Rafieerad (Materials & Design, 2020)
Next-generation “early transition metal carbides and nitrides” (MXene) materials have facile and economic processing with simultaneous synthesis and functionalization. Their surface characteristics can be tailored for specific applications, including energy storage, sensors, and water filtration, by adjusting synthetic parameters. Furthermore, MXene possesses excellent biocompatibility and can be designed for anticancer, antibacterial, and immunomodulatory properties. However, a major limitation facing systemic delivery of nanoparticles is ensuring successful uptake from the bloodstream into the desired site of action. An important consideration is the vascular endothelial cell (EC), which serves as the barrier between blood and organs. Therefore, cellular uptake of engineered nanoparticles by EC is important to advance their use in nanomedicine. In this study, smart zero-dimensional biocompatible titanium carbide (Ti3C2Tx) MXene quantum dots (MQD) were synthesized with specific surface modifications for subcellular nanomedicine applications. MQD were shown to be spontaneously uptaken into human ECs within 24 h of cell culture. MQD localization was observed to be highly stable during this with no significant changes seen in cell morphology. Furthermore, uptaken MQD maintained their strong autofluorescence properties at different excitation-emission wavelengths to enable post-delivery monitoring and tracking. This novel finding represents promising progress in the application of MQD for nanomedicine.